Numerical Model Analysis of Myring–Savonius wind turbines - Saleh, M.; Szodrai, Ferenc (International Journal of Engineering and Management Sciences, 2019)
Nowadays the importance of renewable energy is growing, and the utilization of the low wind energy potential is getting crucial. There are turbines with low and high tip speed ratio. Turbines with low tip speed ratio such as the Savonius wind turbine can generate adequate amount of torque at low wind velocities. These types of turbines are also called drag machines. The geometry of the blade can greatly influence the efficiency of the device. With Computational Fluid Dynamics (CFD) method, several optimizations can be done before the production. In our paper the Savonius wind turbine blade geometry was based on the so-called Myring equation. The primary objective of this paper was to increase the power coefficient by modelling the effect of the wind on the turbine blade. For the sake of simplicity, a 2D cross-sectional area was investigated in the simulation with ANSYS CFX 19.1.